TINJAUAN MANAJEMEN PENDIDIKAN ATAS PENGARUH KONDISI SOSIAL EKONOMI, PERHATIAN ORANG TUA, DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMP NEGERI 2 SAPURAN KABUPATEN WONOSOBO TAHUN 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine education management review upon the effect of socioeconomic conditions of parents, parental supervision, and learning motivation toward students’ learning achievement in SMP Negeri 2 Sapuran, Wonosobo Regency and determnine the most influential variable on learning achievement. The population was the whole 114 pupils of SMP Negeri 2 Sapuran, all of them as the samples. Data were collected using a questionnaire which was answered directly by the students and the score of the final year test. The data gathered from the questionnaires were analyzed statistically by multiple regression techniques using SPSS. Descriptive percentage of the results showed the majority of respondents stated that the variable of socio-economic conditions of parents and parental attention, were categorized as low, while for the variables of learning motivation were categorized as enough. Then the independent variables such as socio-economic conditions of parents, parental supervision and motivation to learn altogether gained positive score and significant effect on mathematics learning achievement. Partial calculation proved that socio-economic conditions of parents has significant and positive effect on mathematics learning achievement, parental supervision is also shown to has significant and positive effect on mathematics learning achievement, while the results of analysis showed that learning motivation also has significant and positive effect on mathematics learning achievement. This suggests that if the socio-economic conditions of parents, parental supervision, and motivation to learn increases, the mathematics learning achievement will also increase.